INTERNALISASI NILAI-NILAI AKHLAK MELALUI PENDEKATAN INTEGRATIF DI SMAN 2 LAMBU BIMA - Junaidin Junaidin (Prodi PAI STIT Sunan Giri Bima, 2023)
This research is a descriptive qualitative research which aims to examine the success of SMAN 2 Lambu in internalizing moral values ​​through an integrative approach. Data collection methods used are observation, interviews, and documentation. The instruments used are in the form of researchers as the main instrument, observation guides, interview guides, and google forms, as well as documents and other supporting tools. Data processing techniques start from collecting data, condensing data, organizing data, and verifying data. Data in quantitative form will be processed first with the percentage formula so that it can be described, while data in qualitative form will be described. Test the validity of the data using triangulation techniques. The results of this study show that first, the process of internalizing moral values ​​through an integrative approach at SMAN 2 Lambu is actually still limited to a combination of concepts between Islamic Religious Education, language, social morality (IPS) and clashes with medical views or natural phenomena around (IPA). Second, the obstacles to the process of internalizing moral values ​​through an integrative approach encounter several obstacles, such as a) It lies with the teacher and students, namely students must master the prioritized concepts, attitudes and skills. b) Its application, namely the difficulty of fully implementing this type. c) this type requires a study team, both in planning and implementing it. d) Integrating the curriculum with concepts from each field of study requires a variety of learning resources. Third, the results of internalizing moral values ​​through an integrative approach carried out by PAI teachers received positive responses from all parties. Be it the principal, teachers and students. The values ​​that are formed and internalized to students are none other than; 1) morals to Allah SWT which are manifested through faith and prayer, 2) morals to fellow human beings which are manifested in an attitude of mutual help and tolerance for other students and not hesitate to remind each other of kindness. Like cleanliness, no scribbling or anything like that. 3) and lastly is morals towards the surrounding environment which is reflected in the attitude of maintaining personal hygiene, class and the school environment.